Przestrzenne zróżnicowanie zagrożenia przestępczością w Polsce - Kądziołka, Kinga (De Securitate et Defensione. O Bezpieczeństwie i Obronności, 2016)
The aim of the article is to analyze spatial variation, structure and dynamic of crime rate in Poland. There was presented changes in the structure and dynamic of crime rate in Poland. To identify groups of poviats similar in terms of the intensity of selected categories of crimes there was used Ward’s method. Special attention was paid to the problems associated with the measurement of crime.